Tumour necrosis factor alpha as a therapeutic target for immune-mediated inflammatory diseases. - Taylor, P; Williams, R; Feldmann, M (2004)
Preclinical studies have identified and validated tumour necrosis factor alpha (TNFalpha) as a key disease molecule and therapeutic target for immunotherapeutic intervention in many immune-mediated inflammatory diseases. Clinical indications include rheumatoid arthritis, Crohn's disease, ankylosing spondylitis and psoriasis. Recent clinical findings indicate that many chronic inflammatory disorders share certain pathogenic pathways, whereas others are limited to particular disease phenotypes. Better understanding of these pathogenic pathways will inform the development of new therapeutic approaches leading to more complete and sustained disease remissions.